(untitled) (Journal of Medical & Health Sciences Review, 2026)
Human papillomavirus (HPV) vaccination is an essential public health tool in reducing the incidence of HPV-related cancers, particularly cervical cancer. Despite the proven benefits of the vaccine, vaccination rates among adolescents remain suboptimal globally. School nurses are key figures in promoting vaccination within schools, yet their efforts are hindered by various barriers such as parental resistance, misinformation, lack of training, and limited resources. This qualitative study examines school nurses’ experiences with HPV vaccine promotion, identifying both barriers and facilitators to vaccine advocacy. Semi-structured interviews with 15 school nurses from diverse educational settings reveal key challenges including misinformation, time constraints, and parental objections. Facilitators such as professional training, institutional policies, and collaborative efforts with healthcare providers were also identified. The study underscores the importance of systemic interventions to enhance school nurses’ capacity to advocate for the HPV vaccine effectively. Recommendations are provided to improve training, policy support, and public health collaboration to increase HPV vaccination uptake.